Maximizing Conversion Efficiency: Exploring the Impact of AI Marketing on Sales Funnel Optimization - Holenarsipur, Praveen Madhu (Digital Repository of Theses - SSBM Geneva, 2024)
Artificial Intelligence (AI) is pivotal in digital advertising, enhancing conversion rates and corporate success. While AI's impact on client service, advertising, and logistics management is well-documented, there's growing interest in its nuanced effects on B2B sales, particularly in lead screening. AI tools excel in analyzing vast data sets to identify potential leads. This study aims to explore AI Marketing's influence on Sales Funnel Optimization and Conversion Efficiency. It addresses key questions on how AI impacts these areas, along with associated benefits, challenges, and opportunities. By employing a mixedmethod approach—qualitative interviews and quantitative surveys—the research provides comprehensive insights into AI's role in enhancing sales funnel efficiency and optimizing marketing strategies. Data collection uses purposive sampling. Qualitative data from interviews undergoes thematic analysis, while quantitative data from surveys contributes statistical insights. Descriptive statistics reveal positive perceptions of AI’s role in smoothing sales funnels (mean values higher than 4.0 on a 5-point Likert scale), supported by reliable measures (Cronbach's Alpha = 0.641). Regression analyses highlight AI marketing’s significant contribution (explaining 8.3% variance) in maximizing conversion efficiency. These findings are crucial for marketers aiming to leverage AI for improved operational efficiency, precise customer targeting, and informed decision-making. However, the study acknowledges limitations, including sample size and demographic homogeneity, affecting generalizability. Future research should adopt longitudinal designs with larger, diverse samples to validate findings over time. Further studies should also address ethical considerations in AI marketing and explore models optimizing collaboration between human marketers and AI tools. As technology evolves rapidly, ongoing research will be vital in understanding AI's evolving impact on marketing strategies.